Ki67 and CD31 Differential Expression in Cutaneous T-Cell Lymphoma and Its Mimickers: Association with Clinicopathological Criteria and Disease Advancement - Zohdy M; Abd El hafez A; Abd Allah MYY; Bessar H; Refat S (Dove Medical Press, 2020)
Marwa Zohdy,1 Amal Abd El hafez,2 Mona Younis Youssef Abd Allah,2 Hagar Bessar,3 Sherine Refat2 1Department of Dermatology, Andrology and STDs, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 2Pathology Department, Faculty of Medicine, Mansoura University, Mansoura, Egypt; 3Dermatology, Venerology and Andrology Department, Faculty of Medicine, Zagazig University, Zagazig, EgyptCorrespondence: Amal Abd El hafezPathology Department, Faculty of Medicine, Mansoura University, El-Gomhouria Street, Mansoura-Dakahlia, EgyptTel +201152785705Email amalabdelhafez@gmail.comBackground: Cell proliferation and angiogenesis are important in progression of cancerous processes. Differentiating cutaneous T-cell lymphoma (CTCL) from its mimicking dermatoses and prognosticating it are challenging.Aim: This study assesses cell proliferation and angiogenesis in different CTCL subtypes using immunohistochemistry (IHC) for Ki67 and CD31 to testify their usability in differentiating CTCL from mimicking dermatoses and discriminating CTCL subtypes from each other with correlation to clinicopathological parameters and disease advancement.Patients and Methods: IHC for Ki67 and CD31 were applied to skin biopsies from 81 patients divided into CTCL (n=59) and dermatoses (n=22) groups. Hot-spot analysis was used to score Ki67 and CD31 microvascular density (MVD) semiquantitatively. Statistical analysis was performed to compare Ki67 index and MVD between CTCL and dermatoses. CTCL subgroups were compared to each other. Ki67 index and CD31 were compared to age, gender, skin and nodal involvement, blood tumor burden and TNMB stage.Results and Conclusion: There were significant differences in proliferation index and MVD between dermatoses and CTCL, and between dermatoses and all CTCL subtypes with exception of Ki67 in early mycosis fungoides (MF) and CD31 in patch lesions. Increased cell proliferation and MVD were significantly associated with older age, T3 and 4 skin involvement, significant nodes (N1-3), positive blood tumor burden (B1,2) in CTCL and TNMB stage of MF. Both markers differentiated significantly late from early MF, classic MF from its variants and non-MF CTCL from total MF, but not from late MF. In conclusion, Ki67 and CD31 expression in skin biopsies using IHC reproduces the role of proliferation and angiogenesis in the differential diagnosis and prognostication of CTCL being expressed at higher levels in aggressive than indolent CTCL. Therapeutic targeting of cell proliferation and angiogenesis may improve patient’s outcome in CTCL. Usability of these markers into patient’s stratification should be considered in further studies.Keywords: Ki67, CD31, cutaneous T-cell lymphoma, mycosis fungoides, TNMB stage